Floating Vetiver Island (FVI) and implication for treatment system design of polluted running water - Kusin, F. M.; Hasan, S. N. M. S.; Nordin, N. A.; Mohamat Yusuff, F.; Ibrahim, Z. Z. (Applied Ecological Research and Forensic Institute, 2019)
Floating Vetiver Island (FVI) system has been investigated in this study as a relatively new technology of artificial wetland treatment. Vetiver grass (Vetiveria zizanioides) was used as the treatment vegetation in the FVI owing to its high tolerance to various types of contaminants. Performance of the FVI was tested on actual polluted running water having characterized by a Class III-Class IV river according to water quality index (WQI) classification. Field trial of FVI over a six-week installation demonstrated an improved water quality with significant increase (92%) of dissolved oxygen and great removals of chemical oxygen demand (77%) and nitrate (73%), resulting in 14% increase of the overall WQI. It was proposed that treatment system performance for FVI can be reflected by the number of pontoons (FVIs) and treatment distance required to achieve desired water quality improvement. The calculated pollutant removal rates were incorporated into the estimation of treatment system requirements. Field installation guide for FVI system is also presented along with treatment system maintenance. For such an FVI system, vetiver grass pruning (trimming) at 2-month intervals is recommended for promoting the growth of the plant and for medium- to long-term FVI performance.